Early-age tensile constitutive relationships for steel and polypropylene fiber reinforced concrete. (1st March 2021) - Bhogone, Manjunath V.; Subramaniam, Kolluru V.L.
Highlights: Early-age fracture responses of steel and polypropylene fiber reinforced concrete obtained. Age-dependent stress-crack separation ( σ-w ) relationship of the fiber-reinforced composite material derived. Fibers significantly increase the early-age tensile strength of concrete. Steel fibers significantly increase Young's modulus of the concrete at an early age. Blends of micro and macro polypropylene fibers exhibit improved early-age σ-w relationship. Abstract: Early-age fracture tests are conducted on concrete beams with discrete steel, macro polypropylene and blends of macro and micro polypropylene fibers. The fracture behavior with aging of the concrete matrix containing 0.66% volume fraction of fibers is investigated at 1, 3, 7, and 28 days of age. The age-dependent multi-linear cohesive stress crack-separation ( σ-w ) relationship and the modulus of elasticity of the fiber reinforced composite material are obtained from the measured fractured responses. The generic multi-linear form of the σ-w relationship captures the age dependent variations in the stress with crack opening associated with initial softening and the hardening produced by fibers. The σ-w relationships determined from the fracture responses indicate that all fibers types significantly increase the tensile strength of concrete at 1 day. By 28 days, the tensile strength of the fiber reinforced concrete is comparable to the plain concrete. The steel fibers significantly increase the Young's modulus of the fiber reinforced concrete in the first 3 days. At any age, steel fibers provide the largest σ as a function of w, when compared to the polypropylene fibers. The differences between σ-w responses of the polypropylene and steel fiber reinforced concretes increase with age and there is a steady increase in the fracture energy with age. The improvement in the post-cracking response of steel fibers with age is due to increases in the resistances to crack propagation and pullout of fibers. Blends of micro and macro polypropylene fibers exhibit higher resistance to crack propagation and to pullout of fibers when compared with the macro polypropylene fibers alone.